Health Literacy and Health Outcomes in Chronic Obstructive Pulmonary Disease Patients: An Explorative Study - Azkan Ture, Deniz; Bhattacharya, Sudip; Demirci, Hakan; Yildiz, Tekin (Frontiers in Public Health, 2022)
Aim: The aim of this study was to evaluate the relationship between health literacy and Chronic Obstructive Pulmonary Disease (COPD) severity. Methods: Pulmonary function test, sociodemographic features, Modified Medical Research Council Dyspnea Scale, COPD assessment test and the European Health Literacy Survey Questionnaire were used. The study examined 13,760 patients who underwent a pulmonary function test. Questionnaires were assessed for 336 patients who completed the inclusion criteria. Results: There was a significant decrease in health literacy according to COPD severity (p<0.001). In multivariate analysis, the risk of severe COPD was 2.74 times higher in patients with poor income level than in patients with good income level. In patients with inadequate HL, the risk of developing severe COPD was 1.80 times higher. A significant difference was found in HL index scores among the groups in terms of education level and income level (P<0.001; p <0.001, respectively). The most difficult topics for COPD patients were periodic health examinations, good practices in mental health and adult vaccinations. Conclusions: COPD patients were found to be at a health literacy level well below the expected level. The risk of severe COPD increased with poor income and inadequate HL. Healthcare providers should be careful in accessing, understanding and interpreting health information of patients with inadequate health literacy. Therefore, patient education should be prioritized in the follow-up and treatment of COPD patients. Physicians should pay maximum attention to patients with COPD in the regular use of drugs, their proper use, in taking preventive measures and in vaccination.